Spontaneous pneumomediastinum: an unusual complication of hyperemesis gravidarum. Issue 2 (9th February 2020) - Foley, David; Holmes, Heather J; Kauffman, Robert P
Abstract : A 21-year-old first trimester primagravida woman with hyperemesis gravidarum was noted to have incidental subcutaneous emphysema during thyroid ultrasound. Follow-up radiograph demonstrated supraclavicular subcutaneous emphysema, left apical pneumothorax and pneumomediastinum. The patient was transferred to the intensive care unit and evaluated for esophageal rupture. Because no defects were seen on swallow studies/endoscopy and the patient was stable, she was treated conservatively with antibiotics and monitored. The patient's condition improved, and she was discharged on hospital day 6. Subcutaneous emphysema secondary to hyperemesis gravidarum is a rare but potentially life-threatening condition in which the source of the mediastinal leak needs to be immediately determined. After the more serious sources of mediastinal air have been excluded, conservative management is suitable.